2014
DOI: 10.1037/a0038178
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents misperceive and are influenced by high-status peers’ health risk, deviant, and adaptive behavior.

Abstract: Most peer influence research examines socialization between adolescents and their best friends. Yet, adolescents also are influenced by popular peers, perhaps due to misperceptions of social norms. This research examined the extent to which out-group and in-group adolescents misperceive the frequencies of peers' deviant, health risk, and adaptive behaviors in different reputation-based peer crowds (Study 1) and the prospective associations between perceptions of high status peers' and adolescents' own substanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 51 publications
2
63
0
1
Order By: Relevance
“…Because adolescents might be less likely to indicate that they were bullied themselves than that others were bullied, some aggressive students may not have been nominated, even if they engaged in aggressive behaviors. However, previous studies have also shown that youth generally tend to overestimate their peers' antisocial behavior toward others (Prinstein and Wang 2005), particularly the antisocial behaviors of popular peers (Helms et al 2014). Also, many aggressive acts such as bullying occur in private (e.g., see Olweus 2013), and thus may be best assessed by asking about self-directed aggression.…”
Section: Discussionmentioning
confidence: 99%
“…Because adolescents might be less likely to indicate that they were bullied themselves than that others were bullied, some aggressive students may not have been nominated, even if they engaged in aggressive behaviors. However, previous studies have also shown that youth generally tend to overestimate their peers' antisocial behavior toward others (Prinstein and Wang 2005), particularly the antisocial behaviors of popular peers (Helms et al 2014). Also, many aggressive acts such as bullying occur in private (e.g., see Olweus 2013), and thus may be best assessed by asking about self-directed aggression.…”
Section: Discussionmentioning
confidence: 99%
“…These findings may be explained by Perceptual Control Theory (PCT; Powers, 1973 Barker, 2009;Beyens et al, 2016;Boyd, 2007;Burrow & Rainone, 2017;Chotpitayasunondh & Douglas, 2016;Helms et al, 2014;Kwak, Choi, & Lee, 2014;Mascheroni, Vincent, & Jimenez, 2015;Przybylski et al, 2013;Toma & Hancock, 2013;Utz et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Students were primarily white (63%), black (22%) and East Asian (15%), with an almost even gender split (48/52 female/male) and from diverse socio-economic communities: upper socioeconomic (20%), middle (54%), and lower (26%). This study targeted adolescents due to the: (i) high online usage this age group exhibits, and the vulnerability to peer evaluations and risk behaviours (Helms et al, 2014), (ii) heightened vulnerability to excessive online use, leading potentially to addictive symptoms (Kuss et al, 2013), and (iii) development of body-image concerns and an overemphasis on peer comparisons that may be associated with the development of eating disorders, obesity and dysfunctional exercise (Meier & Gray, 2014;Voelker et al, 2015).…”
Section: Participantsmentioning
confidence: 99%
“…Research conducted on adolescent misperceives and behaviors among students in the school system demonstrated that associate group generalizations are personifications. The study showed that teenagers misinterpret their peers' high-risk practices, and such an understanding encourage young adolescents to behave in a specific way, related to danger (Efstratopoulou et al, 2012;Helms et al, 2014;Jamiu, 2011;Oyerinde, 2004). Reid (1999) found that students who come from poor background engaged in truancy in school, while Gray and Jesson (1990) found that students from the single-parent family have a poorer attendance rate than those from the more traditional family.…”
Section: Literature Reviewmentioning
confidence: 99%